Level of awareness for wind flow assessment in urban development (Malaysia) - Ng, Soo Nee @ Kerry Ng (2010)
A sustainable housing development requires through planning which consider aspect of naturally ventilation buildings, the wind flow around the structure strongly affects the air change rates within the building. Thus, if wind environment that generate sufficient wind speed is design at a neighborhood scale, the energy consumption of air-condition in the area can be significantly reduced. Unfortunately, nowadays development housing not concerns the aspect of wind flow in houses. Besides that, they not realize the wind affects our life in various ways and makes our life comfortable by transporting heat. Unfortunately, public awareness on wind flow is less. This study focused on review of Malaysia's urban planning guidelines, crossreferences with Hong Kong guidelines and level of awareness for wind flow assessment in urban development (Malaysia). The information related with review of Malaysia's urban planning guidelines contained in the Department Of Town and Country Planning Peninsular Malaysia in Town and Country Planning 1976 (Act 172) and Uniform Building By-Law 1984. The objectives of this research were to review the potential of insufficient environmental guidelines and policies required for urban development in Malaysia, to understanding the current policies and guidelines approved in Malaysia urban development and to analyses level of awareness for wind flow assessment in urban development in Malaysia. The data was collected by sending questionnaire and interviews to obtain their response on this issue. Results from the analysis show the level of awareness for wind flow assessment in urban development (Malaysia) is very important to improve the quality of our life. As conclusion, planning guidelines of residential areas must consider all aspect of wind flow because of global warming in order to provide more comfortable life for citizen.